2001
DOI: 10.1515/jpem-2001-0811
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Current Status of Iodine Prophylaxis in Bosnia and Herzegovina Federation

Abstract: Assessment of the status of iodine prophylaxis was studied in 5,523 schoolchildren randomly selected in all cantons in Bosnia and Herzegovina Federation (BHF). According to the iodine content of household salt samples, all cantons of BHF were divided into two groups: Group A: 95.5% of the salt used is produced in the Tuzla plant, in which the salt is iodized at 5-15 mg Kl/kg salt, and 4.5% of the salt used is produced in the Pag plant, in which the salt is iodized at 20-30 mg Kl/kg of salt, and Group B: 19.9% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
6
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…In Bosnia and Herzegovina, the first law requiring an obligatory iodization of all salt for human and animal consumption with 3.75 to 11.25 mg of iodide as potassium iodide (KI) per kilogram of sodium chloride was proclaimed in 1953 [5]. Later studies showed evidence of iodine deficiency [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…In Bosnia and Herzegovina, the first law requiring an obligatory iodization of all salt for human and animal consumption with 3.75 to 11.25 mg of iodide as potassium iodide (KI) per kilogram of sodium chloride was proclaimed in 1953 [5]. Later studies showed evidence of iodine deficiency [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…has been identified as an VOLUME iodine-deficient area and it was concluded that the preventive measures taken so far were not sufficient to correct the iodine deficiency in the population 6 . has been identified as an VOLUME iodine-deficient area and it was concluded that the preventive measures taken so far were not sufficient to correct the iodine deficiency in the population 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Iodine deficiency has been eradicated in the country since 1953, when fortifying table salt with 3.75-11.25 mg of iodide as potassium iodide per kg of sodium chloride started (Tahirovic et al, 2001). Nevertheless, some later studies showed an evidence of iodine deficiency (Filipovic and Siljak, 1974;Tahirovic et al, 2001) why health officials wanted to increase the iodine content of salt, as well as to activate health control programmes focusing on iodine status of schoolchildren (Tahirovic et al, 2001). On 25 th October 2001, Federation of B&H government promulgated the new Regulations on Edible Salt Quality which requires iodization of salt with 20-30 mg of iodine per kg of salt (Anonymous, 2001).…”
mentioning
confidence: 99%
“…Although some important investigations on iodine status in human population, especially children, have been done in the past (Filipovic and Siljak, 1974;Tahirovic et al, 2001; Toromanovic and Tahirovic, 2004), data on the iodine nutrition of humans and animals in B&H are still very scarce. The relative contribution of different foods in the diet to the total daily intake of iodine is not known, except for table salt, because the iodine concentration in foods, including milk, or feeds has never been investigated.…”
mentioning
confidence: 99%